2022
DOI: 10.3389/fmicb.2022.946463
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cows Experimentally Infected With Bovine Leukemia Virus Showed an Increased Milk Production in Lactation Numbers 3–4: A 4-Year Longitudinal Study

Abstract: Bovine leukemia virus (BLV) is widespread in global cattle populations, but the effects of its infection on milk quantity and quality have not been clearly elucidated in animal models. In this study, 30 healthy first-lactation cows were selected from ≈2,988 cows in a BLV-free farm with the same criteria of parity, age, lactation number, as well as milk yield, SCS, and composition (fat, protein, and lactose). Subsequently, these cows were randomly assigned to the intervention (n = 15) or control (n = 15) group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…In this study, BLV infection had a positive effect on milk yield when analyzed considering farm differences, calving number, and lactation period. An experimental study of BLV infection reported that BLV-positive dams produced more milk, which is consistent with our report [38]. Additionally, a field study reported that herds with higher BLV prevalence actually produce more milk [40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, BLV infection had a positive effect on milk yield when analyzed considering farm differences, calving number, and lactation period. An experimental study of BLV infection reported that BLV-positive dams produced more milk, which is consistent with our report [38]. Additionally, a field study reported that herds with higher BLV prevalence actually produce more milk [40].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported the impact of BLV infection and BoLA-DRB3 on cattle productivity [4][5][6][7][19][20][21][22][23][24]38,[40][41][42][43]. Results from previous studies differed with regards to BLV infection, where it was found to have positive, negative, as well as no effect on cattle productivity [4][5][6][7]38,[40][41][42][43]. Additionally, BoLA-DRB3 reportedly has positive or negative effects on dairy cattle productivity [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the diagnosis of mastitis, these Holstein dairy cattle all had the same lactation number and had comparable individual performance and ages ( Table 1 ). In addition, with commercial ELISAs (Qiaodu, Shanghai, China) or PCRs ( Yang et al, 2022 ), it was preliminarily determined that none of the experimental cows infected any of the following pathogens: S. aureus ( Yang and Laven, 2022 ), Bacillus cereus ( Simbotwe et al, 2018 ), Streptococcus agalactiae ( Bu et al, 2015 ), Babesia spp., Brucella abortus , Anaplasma spp., or Theileria spp.…”
Section: Methodsmentioning
confidence: 99%
“…Other research demonstrated that milk production in BLV-positive cows is comparable to that of healthy cows, and, in some cases, it may even be higher [13,205]. Additionally, a four-year study on the milking performance of cows experimentally infected with BLV reported that artificial infection with BLV can actually enhance the milk yield of dairy cows [206]. Hence, further research is necessary to thoroughly understand the impact of BLV infection on milk production in dairy cows and its underlying mechanisms.…”
Section: Effects On the Milk Production And Milk Quality Of Dairy Cowsmentioning
confidence: 99%